2022
DOI: 10.32604/cmc.2022.021724
|View full text |Cite
|
Sign up to set email alerts
|

Beamforming Performance Analysis of Millimeter-Wave 5G Wireless Networks

Abstract: With the rapid growth in the number of mobile devices and user connectivity, the demand for higher system capacity and improved qualityof-service is required. As the demand for high-speed wireless communication grows, numerous modulation techniques in the frequency, temporal, and spatial domains, such as orthogonal frequency division multiplexing (OFDM), time division multiple access (TDMA), space division multiple access (SDMA), and multiple-input multiple-output (MIMO), are being developed. Along with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, when calculating direct trust and third-party trust in this model, only a simple arithmetic average and a single credible value were used, which was too rough to effectively prevent various attacks by malicious entities in the network against the trust system itself. Saraereh et al [7] combined Bayesian networks with entropy theory (ET) and offered a lightweight trust model for wireless sensor networks. The authors suggested that the weights of different trust aspects were derived from ET rather than setting manually.…”
Section: Related Workmentioning
confidence: 99%
“…However, when calculating direct trust and third-party trust in this model, only a simple arithmetic average and a single credible value were used, which was too rough to effectively prevent various attacks by malicious entities in the network against the trust system itself. Saraereh et al [7] combined Bayesian networks with entropy theory (ET) and offered a lightweight trust model for wireless sensor networks. The authors suggested that the weights of different trust aspects were derived from ET rather than setting manually.…”
Section: Related Workmentioning
confidence: 99%
“…Beam-forming is a signal-processing technique that has revolutionized the way we transmit and receive information wirelessly. Beam-forming involves the precise manipulation of the directionality of an antenna or an array of antennas to focus the transmission or reception of signals toward a specific target [1]. Unlike traditional omnidirectional antennas, beamforming empowers systems to transmit and receive data with enhanced precision, reduced interference, and improved signal-to-noise ratios [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Weighty (1) and Weighty(M y ): These terms represent the weights associated with the first and last element in the vertical direction, respectively. Weights are used to adjust the amplitude and phase of signals from each antenna element, contributing to the overall beamforming direction and pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach that allows the antenna to direct radio waves in a particular direction and the receiver is beamforming. Beamforming boosted spectrum efficiency and reduced interference while simultaneously transferring more data from more antennas [ 8 , 9 ]. Furthermore, recently developed waveforms such as FBMC, UFMC, F-OFDM, and GFDM can overcome pulse shaping, filtering, and precoding issues to reduce the out-of-band (OOB) leakage of OFDM signals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%